New observations of the total electron content and ionospheric scintillations over Ho Chi Minh City - Dao, Tam; Huy, Minh Le; Carter, Brett; Le, Que; Trinh, Thanh Thuy; Phan, Bao Ngoc; Otsuka, Yuichi (Vietnam Journal of Earth Sciences, 2020)
In January 2018, a Trimble NetR9 GNSS receiver was installed at International University - Vietnam National University (IU-VNU), which is located at 10°52’N, 106°48’E in Ho Chi Minh City (HCMC). The GNSS signals recorded from the receiver are useful for studying the ionospheric variations over this station as well as the magnetosphere-ionosphere coupling effects, therefore, we aim to preliminarily process and evaluate data recorded from this new station. Based on the data obtained with this GNSS receiver, we first estimated the total electron content (TEC) using the carrier-phase method which is a combination of code and phase measurements. We then calculated the rate of change of TEC index (ROTI) with respect to time and investigated its day-to-day variations. Our results show some typical features in the diurnal and seasonal TEC and ionospheric scintillation variations during 2018-2019. The distributions of ROTI over these two years of solar minimum show significant occurrences of scintillation, which are caused by small-scale ionospheric irregularities in the equatorial ionosphere. In addition, we found a significant increase of TEC in the latest strong geomagnetic storm in August 2018. The disturbance dynamo appears to have suppressed plasma bubbles after sunset and enhanced their formation at midnight. Thus, the disturbance dynamo effectively caused a delay of ionospheric scintillations. The TEC observed in HCMC also contributes to the data of ground-based observational receiver systems along 105o E longitude for studying ionospheric variations in low-latitude and equatorial regions. Our preliminary results indicate that the GNSS data collected at IU-VNU station is a valuable reference dataset for further research of the ionosphere.